Analyzing a four-layer green supply chain imperfect production inventory model for green products under type-2 fuzzy credit period. (March 2019) - Panja, Subrata; Mondal, Shyamal Kumar
Highlights: A four-layer supply chain and a concept of green supply chain has been included in the inventory model. More realistic quantity dependent credit period has been structured. Green degree dependent production cost has been considered. Customers demand is a function of green degree and retailer's selling price. A generalized type-2 fuzzy credit period is constructed and an efficient defuzzification algorithm is presented. Abstract: Now-a-days, green supply chain has become an inspiring concept to study an integrated inventory system. Due to environmental worry, the acceptability of green products into today's competitive market is on the rise. Therefore, this study focuses on the determination of the green degree of a finished product in an imperfect production system, where production cost depends on the green degree of the produced product. This research, for the first time, looks into the optimum number of business cycles and raw-materials replenishment cycle in an integrated production inventory model in green supply chain with two-level credit period. The supply chain consists of a raw-materials supplier, a manufacturer and a retailer, where the supplier offers a quantity dependent credit period to the manufacturer and the retailer is also facilitated with a credit period by the manufacturer. In this paper, retailer's credit period has been considered in type-2 fuzzy nature. Here, the manufacturer produces green products in an imperfect production system where the rate of perfectness of a product depends on production rate and time. The retailer receives good finished products from the manufacturer and fulfills the demand of the customers, where customer's demand is a function of green degree and wholesale price of the retailer. An efficient defuzzification algorithm has been presented to get the defuzzified profit of the integrated type-2 fuzzy profit function. Finally, sensitivity analysis is provided and some managerial insights are concluded for crisp and fuzzy scenario of the model.